(untitled) (Asian Journal of Pharmaceutics (AJP), 2024)
Since ages, plants have had a pivotal role as medicine due to their therapeutic value. Tinospora cordifolia is a well-known plant with versatile medicinal properties including hypoglycemic, anti-inflammatory, antioxidant, immunomodulatory, and antimicrobial, which can be attributed to its secondary metabolites. Viral infections constitute a major faction of human diseases. Developing efficient and novel therapeutic agents to combat viral diseases is an ongoing process, wherein plant-derived natural products are a potential source. T. cordifolia has been explored for its use in viral infections as an immunomodulatory and antiviral agent. Bioactive components of the plant, such as berberine, tinosponone, tinocordiside, isocolumbin, magnoflorine, tinosporin, and cordiofoliside have been reported to exhibit antiviral efficacy. The present review summarizes the efficacy of T. cordifolia as an anti-viral agent and its role in combating viral infections.